2018
DOI: 10.1177/0269215518791274
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vestibular rehabilitation on dizziness and balance problems in patients after traumatic brain injury: a randomized controlled trial

Abstract: The intervention appeared to speed up recovery for patients with dizziness and balance problems after traumatic brain injury. However, the benefits had dissipated two months after the end of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(142 citation statements)
references
References 31 publications
5
95
0
20
Order By: Relevance
“…30 In a pilot randomized trial, exercise may 31 Patients postmild head injury (concussion) experience both symptomatic and functional improvements after VR. [32][33][34] Others have reported that VR may speed up recovery after concussion. 34 Factors that may affect outcome negatively for patients postconcussion include immediate dizziness, 35 larger changes in gait speed and cadence with dual tasks while walking, 36 anxiety or depression, 37 greater number of symptoms and symptom severity, 38 and the complaint of fogginess.…”
Section: Central Vestibular Disordersmentioning
confidence: 99%
“…30 In a pilot randomized trial, exercise may 31 Patients postmild head injury (concussion) experience both symptomatic and functional improvements after VR. [32][33][34] Others have reported that VR may speed up recovery after concussion. 34 Factors that may affect outcome negatively for patients postconcussion include immediate dizziness, 35 larger changes in gait speed and cadence with dual tasks while walking, 36 anxiety or depression, 37 greater number of symptoms and symptom severity, 38 and the complaint of fogginess.…”
Section: Central Vestibular Disordersmentioning
confidence: 99%
“…In this scenario, it is better to randomly assign separate groups for training and placebo, as done by some studies of vestibular therapy in mTBI. 86,87 Eighth, the statistical analyses relied on multiple t tests comparing initial and post-training assessments, without correction for multiple comparisons. For example, there were 8 laboratory-based measures of vergence, and Bonferroni adjustment would set significance at p < 0.006.…”
Section: The Ciuffreda Group's Studies Of 2013 / 2014mentioning
confidence: 99%
“…The PICOS approach (Patients, Intervention, Control, Outcomes, and Study design) was followed (Liberati et al, 2009). Eight studies met the inclusion criteria (Peters et al, 2014;Damiano et al, 2016;Kleffelgaard et al, 2018;Cuthbert et al, 2014;Straudi et al, 2017;Cuff et al, 2014;Sveistrup et al, 2003;Thornton et al, 2005). A total of 259 patients post-TBI were included in this review, 71 (27.41%) of which were females.…”
Section: Participantsmentioning
confidence: 99%
“…The selected studies used various scales to assess balance ability in patients with TBI. The scales that were used: Berg Balance Scale (BBS) (Peters et al, 2014;Cuthbert et al, 2014), Dynamic Gait Analysis (DGI) (Peters et al, 2014), Limits of Stability-Reaction Time Backwards LOS (RT-B) (Damiano et al, 2016), Motor Control Test (MCT) (Damiano et al, 2016), Balance Error Scoring System (BBES) (Kleffelgaard et al, 2018), Unified Balance Scale (UBS) (Straudi et al, 2017), force platform (Straudi et al, 2017), Self-reported balance scales (Cuff et al, 2014), Community Balance and Mobility Scale (CB&M) (Straudi et al, 2017;Sveistrup et al, 2003), and Activities-specific Balance Confidence Scale (ABC) (Thornton et al, 2005). Outcome measures details was described in Table 3.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation